Evaluating (and Improving) Sentence Alignment under Noisy Conditions - Zaidan, Omar; Chowdhary, Vishal (Eighth Workshop on Statistical Machine Translation, 2013)
Sentence alignment is an important step in the preparation of parallel data. Most aligners do not perform very well when the input is a noisy, rather than a highly-parallel, document pair. Evaluating aligners under noisy conditions would seem to require creating an evaluation dataset by manually annotating a noisy document for gold-standard alignments. Such a costly process hinders our ability to evaluate an aligner under various types and levels of noise. In this paper, we propose a new evaluation framework for sentence aligners, which is particularly suitable for noisy-data evaluation. Our approach is unique as it requires no manual labeling, instead relying on small parallel datasets (already at the disposal of MT researchers) to generate many evaluation datasets that mimic a variety of noisy conditions. We use our framework to perform a comprehensive comparison of three aligners under noisy conditions. Furthermore, our framework facilitates the fine-tuning of a state-of-the-art sentence aligner, allowing us to substantially increase its recall rates by anywhere from 5% to 14% (absolute) across several language pairs.